Evaluating the Bibliometric Landscape of Education and Communication for Disability Research - Rahmadewi, Aldila Luthfiana; Maksum, Muh. Nur Rochim; Shobahiya, Mahasri; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to map the development and direction of Communication for Education Research in Scopus-indexed publications. This research utilizes bibliometric examination strategies to investigate all distributions listed in the Scopus data set on Education and Communication for Disability from 1968 to 2023. The information was broken down utilizing Succeed and R/R-Studio. VOSviewer was utilized to break down the simultaneous occurrence of keywords and document citations visually. The authors found 1,165 publications that matched the defined function, subject, and criteria. The results showed an annual growth rate of 8.82%, with the most publications on (theme) in 2022. The US leads the publications with 560 documents. The UK follows them with 130 documents. There is a rapid increase, which is the peak of the number of publications in 2022. Jayanthi, M, Yoder, P J., and Warren, S.F. lead with seven documents each, followed by Epstein, M.H. with six documents. The bibliometric analysis conducted was limited to Scopus data. Other national and international databases should have been considered in this study. This study presents a concise outline of the writing open to scientists working in correspondence and schooling for the handicapped and gives suggestions for future examination.